Conversational Opening Structure in English and Vietnamese - Hoang, Tra My (H. : ĐHQGHN, 2019)
This study aims to describe and compare the opening structures of English and Vietnamese conversations. The study is based on 214 English and 197 Vietnamese staffmanager conversations occurring in office settings gathered in movies. From Schegloff’s (1968) framework, the method of qualitative content analysis is applied to code the data manually and to find out opening sequences and the ways of combining these sequences to construct an opening section used by American and Vietnamese staff and managers. The findings indicate that, unlike Schegloff’s framework, the American and Vietnamese parties construct an opening section from four sequences namely summons-answer, greeting, phatic communication and topic initiation. One-sequence and two-sequence opening structures are by far more frequently deployed than three-sequence and four-sequence opening structures by both the American and Vietnamese subjects. However, the ways of employing and combining particular sequences by both parties are dissimilar